Unintended effects of national-based active labour market policies - Carlo Altavilla; Floro Ernesto Caroleo (Institute for the Study of Labor (IZA), 2009)
Labour market policies settled at national level imply a one-size-fits-all labour market strategy. This strategy might not sufficiently take into account region-specific economic structures. In this paper we employ a panel factor-augmented vector autoregression (FAVAR) to evaluate whether active labour market programs (ALMPs) might asymmetrically affect labour markets at regional level. Given the significant difference between Italian regional economies we separately analyse two areas: the Centre-North and the South. Our results suggest that the timing and magnitude of the reaction of employment rate to ALMP shocks in the two areas is substantially different. Moreover, forecast error variance decomposition highlight that different variables seem to drive employment dynamics. In the South employment is mainly driven by its own shocks and by social and economic context variables. By contrast, in the northern regions, the employment dynamics is significantly explained by the dynamics of nominal and policy variables such as remunerations and ALMP.
urn:nbn:de:101:1-20090323143
Keywords: C33; J64; 330; Active Labour Market Policies; FAVAR; Arbeitsmarktpolitik; Wirkungsanalyse; Regionale Inzidenz; Regionaler Arbeitsmarkt; Beschäftigungseffekt; Italien